Penambahan Serbuk Kayu Kamper terhadap Kuat Tekan Beton - Lydia Darmiyanti; Gali Pribadi; Achmad Pahrul Rodji (Universitas Islam 45, 2021)
Sawdust waste from the furniture industry should be considered. Nowadays, the increased demand for furniture is in line with the increase in sawdust waste produced. Therefore, it is necessary to make use of sawdust to protect environment. An alternative use is the addition of sawdust as the concrete mixture. Cellulose and hemicellulose compounds are compounds contained in wood powder, where these compounds can provide additional bonding between particles in the cement and sand mixture in concrete. Therefore, concrete can be stronger as well as more water resistant, hence it can be used for a specific purpose in constructions. This study aims to analyze the compressive strength of concrete due to the addition of sawdust as an organic fiber in the concrete mixture with the percentage of 0.25%, 0.50%, 0.75% and 1% as substitution of sand. Organic fibers as additives in concrete are being developed until recently. The proposed concrete was 25 MPa quality. Result showed the increase in the compressive strength of concrete by 0.98% in 1% wood powder mixed at 28 days of concrete age.